Skills for New Managers - Stettner, Morey (McGraw-Hill's AccessEngineering., 2000)
Skills for New Managers will show you how to succeed and flourish as a manager. This succinct, highly focused model for effective management will help you master topics including: hiring?how to uncover and hire people who will shine and make you look good; criticism and discipline?tips on how to carry out two of the most difficult, but essential, aspects of management; leadership?strategies and behavior styles for mentoring, coaching, problem resolution. Effective management skills can be learned. Skills for New Managers will give you everything you need to create your own management style, use that style to promote solid performance in your employees, and take the next critical step in your climb up the career ladder.